Degradable starch microsphere transarterial chemoembolization as salvage therapy in patients with uveal melanoma liver metastases - Steinberg, Hannah Luisa; Haubold, Johannes; Bauer, Sebastian; Richly, Heike; Siveke, Jens T.; Wimmer, Julia; Umutlu, Lale; Schaarschmidt, Benedikt M.; Theysohn, Jens M.; Ludwig, Johannes Maximilian (Journal of vascular and interventional radiology, 2025)
Purpose - To assess degradable starch microsphere (DSM) transarterial chemoembolization (TACE) retrospectively as salvage therapy in patients with unresectable uveal melanoma (UM) liver metastases and identify prognostic factors for survival. - Materials and Methods - Fifty-five patients (49.1% male; median age, 65 years) who underwent a median of 2 DSM-TACE treatments (range, 1-12) were included. Cox proportional hazards models for univariate analysis and multivariate analysis and Kaplan-Meier analysis were performed to determine the median overall survival (mOS) and time to progression (TTP) (95% CI). Response assessment was performed according to the Response Evaluation Criteria in Solid Tumours (RECIST) 1.1 criteria. - Results - The mOS of the study cohort was 8.0 months (95% confidence interval [CI], 6.7-9.3). Univariate analysis identified a low lactate dehydrogenase (LDH) level (<2 times the upper level of normal) (hazard ratio [HR] 0.26, 95% CI 0.12-0.57, P < .001), normal serum protein level (HR 0.32, 95% CI 0.15-0.7, P = .008), hepatic tumor burden of ≤25% (HR 0.39, 95%CI 0.19-0.78, P = .007), and monthly tumor growth rate (TGR) of ≤20% before the first DSM-TACE (HR 0.32, 95% CI 0.14-0.7, P = .005) as predictors of prolonged mOS. Multivariate analysis confirmed a low LDH level (mOS, 11.4 vs 4.3 months; P = .021) and low TGR (mOS, 9.9 vs 6.4 months; P = .005) as independent predictors. The median TTP was 4 months (95% CI, 3.1-5.7). The best response observed was partial response in 13.6%, stable disease in 65.9%, and progressive disease in 20.5%, with mOS times of 25 (95% CI, 13.5-31.6), 8.0 (95% CI, 7.1-9.8), and 4.4 (95% CI, 2.1-20.4) months, respectively. - Conclusions - DSM-TACE represents a salvage treatment option for patients with UM with liver metastases that can help control the tumor. Lower pretreatment serum LDH levels and low TGR have been associated with prolonged mOS. However, direct comparison with alternative treatments is required.